THE INFLUENCE OF URBAN STREET FURNITURE TOWARDS HOMELESS IN KUALA LUMPUR, MALAYSIA - Amir, Atikah Raihanah; Ayob, Zulkefle; Abdul Shukor, Fatin Syazwina; Saari, Mohamad Firdaus (PLANNING MALAYSIA, 2024)
Urban street furniture stands as a silent yet influential force in shaping the city's landscape and the lives of its residents. By studying urban street furniture in the context of homelessness, urban planners can work towards creating more inclusive cities for sustainable urban development. Thus, this qualitative research utilised three methods for data collection: literature review, semi-structured interviews, and participant observation. This comprehensive approach aimed to thoroughly understand the relationship between urban street furniture and the experiences of the homeless population in Kuala Lumpur, Malaysia. The findings of the observation in the case study, followed by the interviewed survey, revealed the multifaceted impact of urban street furniture on homeless individuals. Recognising and incorporating features such as comfortable seating, proper lighting, multi-functional planter boxes, access to clean water, and enhanced mobility through transportation hubs can all contribute to creating more supportive and inclusive urban environments for those experiencing homelessness.